2003
DOI: 10.1016/s0042-6822(03)00461-6
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to low infective doses of HCV induces cellular immune responses without consistently detectable viremia or seroconversion in chimpanzees

Abstract: In hepatitis C virus (HCV) infection, there is accumulating data suggesting the presence of cellular immune responses to HCV in exposed but seemingly uninfected populations. Some studies have suggested cross-reactive antigens rather than prior HCV exposure as the main reason for the immune responses. In this study we address this question by analyzing the immune response of chimpanzees that have been sequentially exposed to increasing doses of HCV virions. The level of viremia, as well as the immune responses … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
62
0
1

Year Published

2004
2004
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(73 citation statements)
references
References 65 publications
10
62
0
1
Order By: Relevance
“…No healthy controls (0 of 20) mounted a significant response to any HCV-specific antigen (mean SI core , 1.0; SI NS3 , 0.8; SI NS4 , 0.9; SI NS5 , 0.8 [data not shown]). CD4 ϩ and CD8 ϩ depletion assays performed as previously described (29,30), using paramagnetic microbeads conjugated to a monoclonal mouse anti-human anti-CD8 ϩ or anti-CD4 ϩ antibody (Micro Beads), showed that proliferative responses are mediated by CD4 ϩ cells (data not shown).…”
Section: Methodsmentioning
confidence: 94%
See 1 more Smart Citation
“…No healthy controls (0 of 20) mounted a significant response to any HCV-specific antigen (mean SI core , 1.0; SI NS3 , 0.8; SI NS4 , 0.9; SI NS5 , 0.8 [data not shown]). CD4 ϩ and CD8 ϩ depletion assays performed as previously described (29,30), using paramagnetic microbeads conjugated to a monoclonal mouse anti-human anti-CD8 ϩ or anti-CD4 ϩ antibody (Micro Beads), showed that proliferative responses are mediated by CD4 ϩ cells (data not shown).…”
Section: Methodsmentioning
confidence: 94%
“…The CD4 ϩ or CD8 ϩ T-cell populations were isolated from the PBMC by positive selection using paramagnetic microbeads conjugated to a monoclonal mouse anti-human anti-CD8 ϩ or anti-CD4 ϩ antibody (Micro Beads; Miltenyl Biotec, Bergisch Gladbach, Germany) as previously described (29,30). The viability and purity of isolated CD4 ϩ or CD8 ϩ T-cell populations were checked by flow cytometry, which revealed more than 95% purity.…”
Section: Methodsmentioning
confidence: 99%
“…CMI responses to sub-clinical infection without seroconversion have been reported in HCV Freeman et al, 2004;Post et al, 2004;Semmo et al, 2005;Shata et al, 2003b), and HIV (Alimonti et al, 2006;Clerici and Shearer, 1996;Dittmer et al, 1996;Fowke et al, 1996;Kaul et al, 2004) infections. Memory CMI responses are also long lasting and could be detected up to 20-30 years after exposure despite the decrease of humoral immune responses.…”
Section: Introductionmentioning
confidence: 94%
“…To estimate the number of HEV-specific interferon-γ secreting cells (ISC), PBMC were added at different concentrations (10 4 -10 5 cells/well) in a 100 μl volume of complete medium (RPMI-1640 containing 10% AB + serum). For stimulation, PBMC were pulsed with the test peptides or HEV ORF2 protein at 1-5 μg/ml as described (Shata et al, 2002(Shata et al, ,2003b. After an 18-hour incubation at 37 °C, the plates were washed 5 times with washing buffer (PBS containing 0.5% (v/v) Tween 20; Sigma, St. Louis, MO).…”
Section: Interferon-γ Elispot Assaymentioning
confidence: 99%
“…56 In fact, there exists a subpopulation of individuals exposed to HCV that clear the virus without the induction of anti-HCV antibodies; therefore, the only surrogate markers for HCV exposure in such persons are HCV-specific cell-mediated immune responses. [57][58][59][60][61][62][63] …”
Section: Humoral Immune Responsesmentioning
confidence: 99%